2001
DOI: 10.1016/s0306-5456(00)00123-6
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional changes in the lower urinary tract during pregnancy

Abstract: Objective To assess the prevalence and the development of urinary incontinence in nulliparous pregnant women, both subjectively and objectively, and to investigate the relation of incontinence with the mobility of the urethro-vesical junction measured by perineal ultrasound. Design A prospective longitudinal study.Setting University Hospital and Martini Hospital Groningen, the Netherlands. Population A cohort of 117 nulliparous pregnant women and 27 nulliparous non-pregnant controls.Methods Urinary incontinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
(36 reference statements)
5
38
1
5
Order By: Relevance
“…who had findings of 49%. However, most studies show a smaller prevalence 6,7,10,17 . Nocturnal enuresis was reported by 5.2% of pregnant women, a percentage that was similar to that described by Scarpa et al 5 .…”
Section: Discussionsupporting
confidence: 69%
“…who had findings of 49%. However, most studies show a smaller prevalence 6,7,10,17 . Nocturnal enuresis was reported by 5.2% of pregnant women, a percentage that was similar to that described by Scarpa et al 5 .…”
Section: Discussionsupporting
confidence: 69%
“…This damage reduces PFM strength and may lead to increased bladder-neck and urethral mobility [63, 64] and cause mobility of the urethrovesical junction [11]. Wijma et al [65] found increased bladder-neck mobility from early pregnancy onward to near term. Jundt et al [66] found that pregnant women with SUI had more a mobile bladder neck than continent pregnant women.…”
Section: Pathophysiology Of Stress Urinary Incontinence During Pregnancymentioning
confidence: 99%
“…They put direct pressure on the bladder, which may lead to changing the bladder-neck position [66] and reducing bladder capacity, contributing to bladder pressure that exceeds urethral pressure [65, 83]. This results in urine leakage.…”
Section: Pathophysiology Of Stress Urinary Incontinence During Pregnancymentioning
confidence: 99%
“…These studies have demonstrated moderate to almost perfect reliability for measuring levator hiatal dimensions and substantial reliability for levator–urethra gap (LUG) measurements, the latter being associated with levator avulsion. However, since hormonal influences in pregnancy lead to alterations in connective tissue and pelvic floor function, the quality of ultrasound images may differ from that in non‐pregnant women, which may affect the reliability of these measurements. In addition, there is insufficient knowledge about the amount of training and experience necessary for competence in obtaining these measurements using 3D/4D ultrasound; investigating the learning process could assist specialists who would like to perform them.…”
Section: Introductionmentioning
confidence: 99%